Empowering tax knowledge through collaborative teaching and alumni engagement - Mansor, Norul Akma; Shamsudin, Siti Marlia; Alwi, Fatimah; Khair Anwar, Irda Syahira; Mohd Isa, Noor Saatila (Universiti Teknologi MARA, Kedah, 2024)
Tax laws can be extremely complex and vary widely between jurisdictions. This complexity can make it difficult for individuals and businesses to understand their tax obligations and maximize their benefits. In addition, tax knowledge and regulations frequently change due to new legislation, economic conditions, or political shifts. Keeping up to date with these changes is a challenge for both individuals and professionals. Addressing these issues often involves consulting with tax professionals, such as accountants or tax advisors, who have the expertise to navigate the complexities of tax laws and ensure compliance while optimizing tax outcomes. Recognizing the complexity and frequent changes in tax laws, a team of collaborative lecturers has developed a student program aimed at enhancing tax knowledge, particularly for those preparing for their final exams in taxation. This unique initiative not only involves engagement from the Inland Revenue Board (IRB) but also features a speaker who is an alumnus of the university. Additionally, the program received sponsorship from the Human Resource Development Corporation (HRD Corp) as part of National Training Week (NTW), held from June 24 to June 30, 2024. The half-day session focused on relief and rebate topics and was attended by 594 accountancy students. Feedback from the students indicated that the program was highly beneficial, significantly contributing to their understanding of tax matter Top of Form.